Precise phase control of resonant MOEMS mirrors by comb-drive current feedback. (November 2020) - Brunner, David; Yoo, Han Woong; Schitter, Georg
Abstract: Accurate phase detection and control of nonlinear resonant micro-opto-electro-mechanical system (MOEMS) mirrors are crucial to achieve stable scanning motions and high resolution imaging as needed in precision applications. This paper proposes a precise phase detection method for an electrostatic actuated MOEMS mirror and a novel digital phase locked loop (PLL) that uses an asynchronous logic for high precision driving and immediate phase compensation, while the clock speed is kept low. The phase of the mirror is detected by an amplified current signal, generated by the movement of the comb drive electrodes, transimpedance amplifiers and a simple comparator circuit. An analysis of the proposed detection method reveals that the pointing uncertainty scales with the product of the driving voltage, the curvature of the comb drive capacitance and the angular velocity of the MOEMS mirror at the zero crossing. The developed fast start-up procedure brings the MOEMS mirror to its maximum amplitude within less than 100 ms with a minimum on required prior knowledge of the used device. The low optical pointing uncertainty of 0.3 mdeg obtained in closed loop operation, allows 19000 pixels with a precision of 10 sigma at a scanning frequency of 2 kHz.